학술지와 학술대회의 인용 패턴 비교 분석 : JKIISC 기반 사례 연구 - 김병규(Byungkyu Kim); 박민우(Min-Woo Park); 유범종(Beom-Jong You); 이준(Jun Lee) (한국컴퓨터정보학회논문지, 2024)
본 논문은 ‘정보보호학회논문지’의 참고문헌을 계량서지분석과 사회네트워크분석 방법을 사용하여 학술지와 학술대회의 인용 현황 및 패턴에 관한 비교분석 연구를 수행하였다. 인용 현황 분석결과, 참고문헌에서 학술대회의 비중이 학술지를 약간 상회하며, 약 80%가 해외 출판물로 한국 연구자들의 높은 해외 출판물 의존성이 확인되었다. 인용나이 분석 결과, 즉시인용률이 높아지고 반감기는 길어지며 인용절정기는 짧아지는 경향을 보였다. 특히, 국내 출판물의 즉시인용률이 높고해외 출판물의 반감기가 더 느리게 나타났다. 또한, SCOPUS 학술지 및 ICORE 학술대회 식별과 주제분류를 매핑하여 분석한 결과, 학술지 인용문헌은 컴퓨터과학 (32.3%), 공학 (23.5%), 수학(16.7%), 사회과학 (12.8%)를 포함한 기타 연구분야 (25.6%)로 구성되었으며, 학술대회 인용문헌은‘Cybersecurity and privacy’ 분야의 비중이 가장 높은 가운데 최근에는 ‘Computer Vision and Multimedia Computation’ 및 ‘Machine Learning’ 분야의 인용 증가세가 큰 것으로 조사되었다. 출판물동시 인용 네트워크 분석 결과, 학술대회 그룹이 학술지 그룹보다 연결 중심성 평균값이 높고 해외출판물 그룹이 국내 출판물 그룹보다 더 높았으며, 문헌 유형 간의 동시 인용 빈도는 학술지 내에서 34.3%, 학술대회 내에서 28.8%와 비교하여 학술지와 학술대회 간에서 36.9%로 가장 높게 나타났다. 또한, 동시에 인용된 출판물들과 이들의 연구 분야에 대한 연결 구조를 탐색할 수 있는 네트워크 시각화 지도를 제시하였다. 본 연구의 결과는 국내 정보보안 연구 분야가 학술지와 학술대회문헌을 균형 있게 활용하고 있으며, 이들 간의 상호보완적 관계를 통해 발전하고 있음을 시사한다. This paper conducts a comparative analysis of citation patterns between journals and conferences using bibliometric and social network analysis on references from the ‘Journal of the Korea Institute of Information Security and Cryptology (JKIISC)’. The results indicate that conference references slightly exceed journal references, with around 80% being international publications, highlighting Korean researchers' high dependency on overseas publications. Analysis of citation age shows trends of increasing immediacy citation rate, lengthening citing half-life, and shortening peak time, with domestic publications having higher immediacy citation rate and international publications having slower citing half-life. Mapping SCOPUS journals and ICORE conferences revealed that journal citations mainly come from ‘Computer science’ (32.3%), ‘Engineering’ (23.5%), ‘Mathematics’ (16.7%), and ‘Social Cciences’ (12.8%), along with other research fields (25.6%), while conference citations are predominantly in ‘Cybersecurity and Privacy’ with recent increases in ‘Computer Vision and Multimedia Computation’ and ‘Machine Learning’. Co-citation network analysis shows higher degree centrality for conference groups and international publications. The co-citation frequency between different types of literature was highest between journals and conferences (36.9%), compared to within journals (34.3%) or within conferences (28.8%). Lastly, network visualization maps are presented to explore the structural connections among co-cited publications and their research fields. The results of this study suggest that the field of information security research in Korea effectively balances the use of journal and conference literature, indicating that the field is developing through a complementary relationship between these sources. KCI Citation Count: 0